A Comparison of Continuum and Kinetic Simulations of Moderate pd Microplasmas Integrated With High Secondary Yield Cathodes. Issue 4 (16th September 2016) - Verma, Abhishek Kumar; Alamatsaz, Arghavan; Venkattraman, Ayyaswamy
Abstract : The computational techniques commonly used for low‐temperature plasma simulations are compared in the context of modeling microplasmas driven by cathodes with high secondary electron emission coefficient. Simulations of 100 µm argon microplasmas operating at pressures of 100 Torr and secondary electron emission coefficient of 0.1 are performed using particle‐in‐cell with Monte Carlo collisions (PIC‐MCC), and fluid model using the full‐momentum equations for both electrons and ions. Results obtained for plasma density, potential, electric field, and electron temperature using continuum simulations are compared with the PIC‐MCC simulations as benchmark. The comparison demonstrates significant discrepancies and a need to calibrate continuum simulation parameters based on kinetic simulations. Abstract : Continuum and kinetic simulations of low‐temperature moderate pd microplasmas driven by cathodes with high secondary emission are compared and contrasted with each other. One‐dimensional simulations of a 100 μm argon microplasma performed using the momentum equation for both ions and electrons are compared with particle‐in‐cell with Monte Carlo collision simulations. The discrepancies between the results obtained from the two methods are highlighted.